Your behavior will be monitored - Feinstein, Justin (Tachyon Publications LLC, 2026)
"Megacorporation UniView is poised to cement their reputation as "the most trusted name in AI." After pioneering the world's first widely adopted AI bots, they are barreling toward an audacious new launch. That is, if they can pull it off in time. Enter Noah. A down-and-out copywriter reeling from a midlife crisis, he isn't the typical hire for a groundbreaking tech company full of brilliant engineers and run by a cutthroat CEO. But Lex, UniView's Head of HR and one of their greatest successes, makes no mistakes--her algorithm ensures it. UniView's latest venture--a bot named Quinn that creates revolutionary personalized advertising--needs expert training. Noah needs to teach Quinn--which is a much better student than he ever could have hoped for--the finer points of consumer motivation and the art of writing a catchy tagline. But when corporate competitors force UniView to accelerate its timeline to market, guardrails around the AI loosen just as Quinn seems to be learning a bit too much."--Amazon.